Group Studying vs Personalized Studying - Umaralieva Munojat Mashrabovna; Xasanova Oltinoy Maxammadjon qizi (Journal of Innovation in Education and Social Research, 2023)
This article examines the effectiveness of two prominent learning strategies: group studying and personalized approaches. The paper aims to provide an in depth analysis of the benefits and drawbacks of each method, shedding light on their impact on academic performance, knowledge retention, critical thinking skills, and overall learning experience. By exploring various studies, scholarly articles, and real life examples, this paper aims to help educators, students, and educational institutions make informed decisions about the most suitable learning approach.